Association of interleukin-2, -4 and -10 with dengue severity - Kumar S Abhishek; Anita Chakravarti; C P Baveja; Naresh Kumar; Oves Siddiqui; Suman Kumar (Wolters Kluwer Medknow Publications, 2017)
Background: Dengue is an arboviral disease caused by four distinct serotypes of dengue virus. The pathogenesis of dengue is not very clearly understood. Various pro- and anti-inflammatory cytokines are involved in the immune pathogenesis of dengue. Interleukin (IL)-2/IL-2 receptor interaction is supposed to play a protective role, while IL-4 acts as pro-inflammatory whereas IL-10 acts as anti-inflammatory cytokines. So far, not much information is available regarding the established role of these cytokines with dengue infection and severity. Aims: our study aimed to show the association of IL-2, -4, and -10 with severity of dengue infection. Settings and Design: This was a cross-sectional study. Materials and Methods: The study was conducted in the year 2015; 150 blood samples from suspected dengue cases were confirmed for dengue and then with an equal number of healthy control samples were tested for cytokines levels (IL-2, -4, and -10) by ELISA. Severity of the dengue infection was determined on the basis of clinical manifestations based on the WHO criteria.Statistical Analysis: for statistical analysis, SPSS version 21 (IBM, New York, United States) was used. Results: Out of 150 samples, 56 samples came to be dengue positive. Thirty-eight (67.85%) cases were classified as nonsevere dengue and 18 (32.15%) were severe dengue. The serum levels of IL-4 and -10 were significantly raised in severe dengue cases as compared to nonsevere dengue cases. No significant association was observed between serum IL-2 levels and the severity of dengue. Conclusion: IL-4 and -10 levels can be used as marker of severe dengue and help in early preparedness to start the treatment in the line of severe dengue.